2013
DOI: 10.1002/smll.201301716
|View full text |Cite
|
Sign up to set email alerts
|

Neodymium‐Doped LaF3 Nanoparticles for Fluorescence Bioimaging in the Second Biological Window

Abstract: The future perspective of fluorescence imaging for real in vivo application are based on novel efficient nanoparticles which is able to emit in the second biological window (1000-1400 nm). In this work, the potential application of Nd(3+) -doped LaF(3) (Nd(3+) :LaF(3) ) nanoparticles is reported for fluorescence bioimaging in both the first and second biological windows based on their three main emission channels of Nd(3+) ions: (4) F(3/2) →(4) I(9/2) , (4) F(3/2) →(4) I(11/2) and (4) F(3/2) →(4) I(13/2) that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
125
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 197 publications
(126 citation statements)
references
References 52 publications
0
125
1
Order By: Relevance
“…Two years later, Rocha et al reported the first infrared deep-tissue in vivo image of a mouse after intravenous injection of LaF 3 :Nd 3þ NPs (Figure 1(b)). 34,35 In this case, a preferential accumulation of the Nd:NPs in the liver and the spleen was evidenced by recording (with a Si-based camera) the spatial distribution of the intense 1060 nm fluorescence (corresponding to the 4 F 3/2 ! 4 I 11/2 transition) generated under 808 nm optical excitation.…”
Section: Introductionmentioning
confidence: 99%
“…Two years later, Rocha et al reported the first infrared deep-tissue in vivo image of a mouse after intravenous injection of LaF 3 :Nd 3þ NPs (Figure 1(b)). 34,35 In this case, a preferential accumulation of the Nd:NPs in the liver and the spleen was evidenced by recording (with a Si-based camera) the spatial distribution of the intense 1060 nm fluorescence (corresponding to the 4 F 3/2 ! 4 I 11/2 transition) generated under 808 nm optical excitation.…”
Section: Introductionmentioning
confidence: 99%
“…35 In addition to all these properties, Nd 3þ :LaF 3 NPs also show fluorescence bands with a remarkable thermal sensitivity. 32 Based on all these properties, Nd 3þ :LaF 3 -NPs have been recently used for single cell imaging, sub-tissue thermal sensing, and for in vivo fluorescence imaging.…”
mentioning
confidence: 99%
“…32 Based on all these properties, Nd 3þ :LaF 3 -NPs have been recently used for single cell imaging, sub-tissue thermal sensing, and for in vivo fluorescence imaging. 35 Light-to-heat conversion in Nd 3þ :LaF 3 -NPs, not explored yet, would emerge as an important additional feature that would place Nd 3þ :LaF 3 -NPs in a privilege position among other NPs as they could be used in a multifunctional manner for simultaneous bio-imaging, photo--thermal treatment, and temperature control of the irradiated area, all these facilities with the very same biocompatible nanoprobes.…”
mentioning
confidence: 99%
“…Among lanthanides, Nd 3+ is particularly interesting because it is excited and emits within the first and second biological windows (650 nm -950 nm and 1000-1400 nm), in which the radiation is weakly attenuated by tissues and can penetrate more deeply than the visible light, thus improving the sensitivity of the assays and lowering tissue damage. 6,7,8,9 Most of the Ln 3+ -doped rare earth-based matrices classically studied, such as oxides, vanadates, phosphates, etc., show associated phonon energies that are usually very high resulting in low luminescent efficiencies due to the enhancement of non-radiative pathways. 10 A straightforward solution to this problem came with the development of fluoride-based matrices, which showed a high luminescent efficiency due to their low phonon energies.…”
Section: Introductionmentioning
confidence: 99%